2012
DOI: 10.1111/pin.12001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of EZH2 in renal cell carcinoma as a novel prognostic marker

Abstract: Enhancer of zeste homolog 2 (EZH2) is a member of the Polycomb group proteins and a part of Polycomb repressive complex 2. EZH2 is important for transcriptional regulation through nucleosome modification and interaction with other transcription factors. Particularly, aberration of EZH2 has been implicated in oncogenesis and progression of various neoplasms. The objective of this study was to evaluate EZH2 expression in renal cell carcinoma (RCC), especially clear cell RCC (CRCC) and correlate the expression wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Patients in the study conducted by Laitinen et al (2008) received radiotherapy rather than surgery [ 30 ]. Moreover, 16 studies enrolled patients undergoing surgery but did not provide a clear description of treatments other than surgery[ 14 , 18 , 22 24 , 31 33 , 38 , 43 , 45 , 47 , 49 , 50 , 55 , 61 ]. Thus, a sensitivity analysis was performed in which we excluded these studies, and the HR increased slightly to 2.13 (95% CI: 1.62–2.80; p <0.00001).…”
Section: Resultsmentioning
confidence: 99%
“…Patients in the study conducted by Laitinen et al (2008) received radiotherapy rather than surgery [ 30 ]. Moreover, 16 studies enrolled patients undergoing surgery but did not provide a clear description of treatments other than surgery[ 14 , 18 , 22 24 , 31 33 , 38 , 43 , 45 , 47 , 49 , 50 , 55 , 61 ]. Thus, a sensitivity analysis was performed in which we excluded these studies, and the HR increased slightly to 2.13 (95% CI: 1.62–2.80; p <0.00001).…”
Section: Resultsmentioning
confidence: 99%
“…EZH2, as a catalytic subunit of PRC2, is one of the core components [3,6]. Emerging evidence showed that EZH2 was over-expressed in a wide range of cancers, including ovarian cancer [7], malignant gliomas [8], prostate cancer [9], cervical cancer [10] and renal cell carcinoma [11]. It affected through interacting with other molecules, target genes and signalings.…”
Section: Introductionmentioning
confidence: 99%
“…All of these cases are concerned with beginning, progression, and metastasis of cancer. The increasing of EZH2 expression have been observed in different types of cancer such as prostate 7, breast (8), bladder (9), lung (10), liver (11), kidney (12), stomach (13), esophagus (14). In many of these cases, the expression of EZH 2 is concerned with more increasing in the number and more invasive behavior of cancerous cells, that this behavior is considered as poor prognoses.…”
Section: Introductionmentioning
confidence: 99%